Weight loss in adolescents with down syndrome compared to adolescents with other intellectual disabilities enrolled in an 18-month randomized weight management trial - Ptomey, Lauren T.; Bodde, Amy E.; Hastert, Mary; Suire, Kameron B.; Helsel, Brian C.; Gorczyca, Anna M.; Washburn, Richard A.; Rice, Annie M.; Donnelly, Joseph E. (Frontiers in Pediatrics, 2022)
Background. There is limited information on the efficacy of weight management interventions in adolescents with Down Syndrome (DS) Objective. To compare weight change and intervention compliance between adolescents with DS compared to adolescents with non-DS related intellectual disabilities (ID) who were enrolled in an 18-month weight management trial. Methods. Participants were adolescents (13-21 years) with mild to moderate ID and overweight or obesity. Participants were randomized in a 1:1:1 allocation to one of 3 intervention arms for an 18-month weight management trial: face-to-face/conventional diet (FTF/CD), remote delivery/conventional diet (RD/CD), or remote delivery/enhanced Stop Light Diet (RD/eSLD). Anthropometrics were assessed at baseline 6, 12, and 18 months by staff blinded to the intervention, and self-monitoring data was collected across the 18-month study. As an unpowered, post-hoc, secondary analysis, two-sample t-tests were used to compare the weight change across 6,12, and 18 mos. and compliance across 18 mos. between adolescents with and without DS randomized to each intervention arm. Results. Adolescents with ID (n = 110) were randomized to one of three intervention arms: FTF/CD (n=36, DS = 17, other ID = 19), RD/CD (n=39, DS = 21, other ID = 18) or RD/eSLD (n=35, DS = 15, other ID= 20). Body weight at 18 months was obtained from 82%, 76% and 73% of participants with DS and 84%, 83% and 75% of participants with other ID randomized to the FTF/CD, RD/CD, and RD/eSLD arms, respectively Weight change across 18 months was -0.2 ± 8.8 kg (-0.5%), -0.3 ± 5.3kg (-0.7%), and -2.6 ± 5.0kg (-4.0%) in adolescents with DS randomized to the FTF/CD, RD/CD and RD/eSLD arms, respectively. There were no significant differences in change in body weight or BMI across 18 months between adolescents with DS or those with other ID in any of the 3 intervention arms (all p >0.05). Additionally, there were no significant differences in intervention compliance between adolescents with and without DS across 18 mos. (all p>0.05). Conclusions. Adolescents with DS respond to a multi-component weight management intervention similar to those with others ID